Тристан и Изольда: [роман] / Ж. Бедье ; пер. с фр. А. А. Веселовского - Бедье Ж. (АРГУС, 1993)
Экземпляры: ф.1 (20190523) / Инвентарный номер: 27676 / Цена: 2000.00 / Авт.знак: Б 38 / ГРНТИ: 17.82 / ББК: 84(4Фра)